A panoramic view of a structured how to write for publication course: College students’ views and tips - Erbay Çetinkaya, Şakire (English Education Department, Universitas Islam Indonesia, 2024)
Despite the privileged status of writing in academia, satisfying outputs are still low, and thus lack of knowledge about the nature of academic writing and publishing is attempted to be compensated in how to write for publication courses. Responding to the existing calls to conduct writing-related studies going far beyond diagnosing well-established writing challenges, the current case study seeks to probe 8 MA candidates’ experiences, needs, wishes, and suggestions in a structured how-to-write for publication course through open-ended questionnaires and student diaries at the MA Applied Linguistics program of a large-size state university in Türkiye. The qualitative data of the current study were triangulated with an open-ended questionnaire in the form of participant self-reports and student diaries. The findings show that such writing interventions were valued for adding up to graduate candidates and socializing their writing. However, MA candidates needed to be supported with negotiated workshops as such extensions could help them apply writing theory and find the audience. The insights are provided, and the findings are discussed to suggest implications for both research and educational policy.